(-x)/(-y) = x/y as long as y does not equal 0 in which case it is undefined. x/y cannot be simplified further unless you are given values for x or y or both. For example, if x = 10 and y = 5 then x/y can be simplified to 10/5 = 2.
0.5
x=y
Y divided by X axix- Y/X
wat is the whole problem that actually it is 42
1/x = y x = 1/y
0.5
X divided by -Y is the same as -X divided by Y. Or - (X/Y)
x over y
x=y
X goes into Y is really Y divided by X
It is x^2 + xy + y^2
Y divided by X axix- Y/X
m
X divided by Y
3x over x + y
It is then x/y when simplified
wat is the whole problem that actually it is 42